Shear Strength and Serviceability of GFRP-Reinforced Concrete Beams: A Study on Varying Reinforcement Ratios - Hamed, Thar Mohammed; Said, AbdulMuttalib I. (Salehan Institute of Higher Education, 2025)
This study investigates the behavior of GFRP-reinforced concrete beams with varying reinforcement ratios. The experimental program consists of five concrete beams tested under a simply supported four-point bending setup with a section of (250×300) mm and a clear span of 1800 mm with a span-to-depth ratio of 2.3. The beams were reinforced longitudinally with GFRP bars with varying reinforcement ratios (ρ = 0.5, 0.9, 1.35, 1.8, and 2.25) for B1-B5, respectively. GFRP stirrups were used for the transverse direction with a spacing of 240 mm for all the beams. The results showed that raising the GFRP longitudinal reinforcement ratio to 1.35 enhanced load-carrying capacity performance and dropped at higher reinforcement ratios (1.8, 2.25) while offering better performance in controlling crack widths and deflection, which could be due to the limit of bonding with concrete. Increasing the GFRP longitudinal reinforcement ratio reduced the deflection at both service and ultimate loads with enhanced crack control. Lower reinforcement ratios of (ρ= 0.5) resulted in a brittle failure, wider cracks, and poor stiffness. Conversely, a 1.8 reinforcement ratio led to delayed crack initiation, smaller crack widths, and a balanced stiffness-to-ductility ratio being achieved. It was found that the dowel action of longitudinal GFRP bars greatly contributes to the shear strength of concrete beams, with a ratio of (ρ= 1.35) having the maximum load capacity along the tested beams. The ductility index ranged from 1.7 to 2.49. Higher reinforcement ratio beams resulted in a deeper neutral axis up to (ρ = 1.35), demonstrating improved stress distribution and reduced deformations. Doi: 10.28991/CEJ-2025-011-03-04 Full Text: PDF